THE STUDY OF THE HYDROLICS OF CLOSED SYSTEM POND IRRIGATION IN THE FRAMEWORK OF REVITALIZATION OF PILOT POND IN KARAWANG - (NIM 950 04 003), Hartati
Abstract : The irrigation of Karawang pilot pond is a technical irrigation which is only used for approximately 5 years with a pond area of 250 ha and cultivated with lobsters (udang windu). The system of pond irrigation applied is an open system with change of brackish/ salty water conducted continuously with a total of 10% each day. The business of lobsters (udang windu) cultivation pond with open pond irrigation system was stopped due to failure during harvest time caused by virus attack of white spot. After not being used for more than 10 years, at present, the Karawang pilot pond irrigation is functioned again, by using closed pond irrigation system and cultivating Vannamae type shrimp. Closed pond irrigation system is the use of brackish water repeatedly and the adding of brackish water is conducted at certain times to replace water lost due to evaporation of to maintain water quality in the pond, thus also called closed circulation system. The irrigation of closed system pond is an alternative which may be applied to reduce the possibility of virus attack from the outside because from the aspect of water usage, the pond area is isolated from outside environment and the amount of brackish water used is 58% more efficient than open system. In the framework of revitalization of pilot pond using closed system pond irrigation, besides the repair of destroyed water structure facilities and adjustment of irrigation network using the system applied, a hydrolics study was also conducted, especially the supply of salt water into the mixing pond affected by sea water (tide) rise and fall with hydrodynamic modeling using Hec-Cras program. From the result of hydrodynamic modeling, sea water surface elevation which was not changing significantly between sea water surface at the end of jetti channel to the end of carrier channel or at mixing pond door was obtained. Therefore the data of sea water surface elevation used for hydrolic analysis at mixing pond door is the data of sea water/ tide rises and fall standar procedure to fulfil the requirement of brackish/ salty water quantity and salinity in the mixing pond.